2002
DOI: 10.1086/343055
|View full text |Cite
|
Sign up to set email alerts
|

A Spectroscopic Survey of a Sample of Active M Dwarfs

Abstract: A moderate resolution spectroscopic survey of Fleming's sample of 54 X-ray selected M dwarfs with photometric distances less than 25 pc is presented. Radial and rotation velocities have been measured by fits to the H-alpha profiles. Radial velocities have been measured by cross correlation. Artificial broadening of an observed spectrum has produced a relationship between H-alpha FWHM and rotation speed, which we use to infer rotation speeds for the entire sample by measurement of the H-alpha emission line. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…In all four cases our spectroscopic distance estimates place these stars within or close to the 25 pc radius, in good agreement with the photometric distances predicted by Fleming. G179-055 was found to be a spectroscopic binary (Mochnacki et al 2002). Further stars from Fleming (1998), with proper motions below the NLTT proper motion limit of 0.18 arcsec/yr, will be described in Paper IV.…”
Section: A Possible New Pair That Was Rejectedmentioning
confidence: 96%
“…In all four cases our spectroscopic distance estimates place these stars within or close to the 25 pc radius, in good agreement with the photometric distances predicted by Fleming. G179-055 was found to be a spectroscopic binary (Mochnacki et al 2002). Further stars from Fleming (1998), with proper motions below the NLTT proper motion limit of 0.18 arcsec/yr, will be described in Paper IV.…”
Section: A Possible New Pair That Was Rejectedmentioning
confidence: 96%
“…In this paper we investigate the correlation of activity and rotation for these two samples separately and refer to them as the Volume7 and the Volume14 samples in the text. Griffin et al (1985); Hartmann et al (1987); Hartmann & Stauffer (1989); Rodrìguez (2014); Houdebine (2010Houdebine ( , 2012; Jenkins et al (2009);López-Santiago et al (2010); Malo et al (2014a); Marcy & Chen (1992); Mochnacki et al (2002); Mohanty & Basri (2003); Morales et al (2009);Reid et al (2002); Schlieder et al (2010Schlieder et al ( , 2012a; Stauffer & Hartmann (1986); Stauffer et al (1997);Tokovinin (1992) two subsamples as a function of spectral type is shown in the right-hand panel of Figure 1.…”
Section: Samplesmentioning
confidence: 98%
“…(a) Some other publications and meta-archives that we have searched for potential CARMENES targets are Kirkpatrick et al (1991), Gizis (1997), Gizis & Reid (1997), Gizis et al (2000b), Henry et al (2002Henry et al ( , 2006, Mochnacki et al (2002), Gray et al (2003), Bochanski et al (2005), Crifo et al (2005), Lodieu et al (2005), Scholz et al (2005), Phan-Bao & Bessell (2006), Reylé et al (2006), Riaz et al (2006), Caballero (2007Caballero ( , 2009Caballero ( , 2012, Gatewood & Coban (2009), Shkolnik et al (2009, 2012, Bergfors et al (2010), Johnson et al (2010), Boyd et al (2011), Irwin et al (2011), West et al (2011, Avenhaus et al (2012), Deacon et al (2012), Janson et al (2012, 2014), Frith et al (2013, Jódar et al (2013), Malo et al (2013), Aberasturi et al (2014), Dieterich et al (2014), Riedel et al (2014), Yi et al (2014), , and the DwarfArchive at http://dwarfarchive.org. (b) PMSU: Reid et al (1995Reid et al ( , 2002; Hawley et al (1996); Gizis et al (2002).…”
Section: Carmenes Samplementioning
confidence: 99%